WASIAT WAJIBAH UNTUK CUCU BERAGAMA KRISTEN (STUDI PUTUSAN NOMOR 2401/PDT.G/2022/PA.SBY): Wasiat Wajibah For Christian Grandchildren (Study Of Decision Number 2401/Pdt.G/2022/PA.Sby) - Maryana Putri; Khairani Bakri (Faculty of Law, Universitas Trisakti, 2026)
Islamic inheritance law is the law that regulates the transfer of the deceased’s property to his or her heirs. One of the requirements for inheritance is that the heir must be related by blood to the deceased and be Muslim. One of the developments in Islamic inheritance law is known as wasiat wajibah. Wasiat wajibah is an action taken by a judge to determine the granting of wasiat wajibah to certain parties under certain conditions after the deceased’s death. Thus, the issue at hand is whether a Christian grandchild can receive wasiat wajibah according to Indonesian Islamic inheritance law. The type of research used is normative and descriptive in nature, using secondary data analyzed with qualitative methods and conclusions drawn deductively. In Article 209 of the Compilation of Islamic Law, a mandatory bequest is given to adopted children. A grandchild can only inherit because of their position as a substitute heir. Another requirement for a grandchild to inherit is that they must be Muslim. Therefore, a grandchild who is Christian should not receive a mandatory bequest.